Pancreaticopleural Fistula: A Review - Aswani, Yashant; Hira, Priya (JOP. Journal of the Pancreas, 2015)
Pancreaticopleural fistula is a rare complication of chronic pancreatitis consequent to posterior disruption of the pancreatic duct. The fistulous track ascends into the pleural cavity and gives rise to large volumes of pleural fluid. Pancreaticopleural fistula thus poses a diagnostic problem since the source of pleural fluid is extrathoracic. To further complicate the matter, abdominal pain is seldom the presenting or significant feature. The pleural effusion is typically rapidly accumulating, recurrent and exudative in nature. Pleural fluid amylase in the correct clinical setting virtually clinches the diagnosis. Magnetic resonance cholangiopancreatography, endoscopic retrograde cholangiopancreatography and computed tomography may delineate the fistula and thus aid in diagnosis. Endoscopic retrograde cholangiopancreatography has emerged both as a diagnostic as well as therapeutic modality in select patients of pancreaticopleural fistula while magnetic resonance cholangiopancreatography is the radiological investigation of choice. Besides delineating the ductal anatomy, magnetic resonance cholangiopancreatography can help stratify patients for appropriate management. A near normal or mildly dilated pancreatic duct responds well to chest drainage with octreotide while endoscopic stent placement benefits patients with duct disruption located in head or body of pancreas. Failure of medical or endoscopic therapy calls in for surgical intervention. Besides, a primary surgical management may be tried in patients with complete ductal obstruction, ductal disruption in tail or ductal obstruction proximal to fistula site. Image: Logo of Seth Gordhandas Sunderdas Medical College and King Edward Memorial Hospital. Mumbai, Maharashtra, India.